THE IMPLEMENTATION OF PROJECT-BASED LEARNING TO IMPROVE VOCATIONAL STUDENTS’ SPEAKING SKILLS - Ani Marisah; Rr. Hasti Robiasih (Universitas Sarjanawiyata Tamansiswa, 2017)
This paper aims to describe: (1) the implementation of Project-Based Learning (PBL) to improve students’ speaking skill in SMK N 1 Bantul, (2) the strengths and challenges of the implementation of PBL. This study is an action research consisting of two cycles. The results showed that (1) many students have the opportunity to speak English during the PBL implementation; besides, the students’ interest in learning English increased significantly, (2) the strengths of PBL implementation deals with team work as stimulation for interactions and students could integrate their language skill to social skill and technology. The challenges were: the teacher could not closely assist and monitor the students’ project doing directly. The project making also requires sufficient time. From the results and discussion, it can be concluded that PBL can be used as an alternative learning model since it supports not only language skill improvement but also social and technological skills integration.